Synthesis, Characterization and in vitro Evaluation of Ferrous Phosphate Nanoparticles Loaded Iron for Bioavailability Studies - Renuka Devi, P.; Hemananthan, E. (Asian Journal of Chemistry, 2013)
In the present study, the ferrous phosphate nanoparticles for bioavailability applications in the size of 70-110 nm were prepared by controlled hydrolysis method. The particle size is controlled by the variation of molar ratio, altering the metal salt concentration. The synthesized particles were characterized by XRF and FTIR spectroscopic analysis, to observe the elemental content of the particles. The morphological characteristics were studied using SEM and AFM, which shows the sponge like structure during aggregation and spherical shaped particles when disintegrated, respectively. The size distributions in range of 70-110 nm were observed using centrifugal particle size analyzer (CPS). BET analysis and zeta potential analysis showed the maximum surface area of 220 m2/g and positive charge of +6.2 mV, respectively for the stoichiometric reaction synthesis. Low particle size and high surface area are the advantageous factor of the particles for the bioavailability analysis, obtained by stoichiometric concentration. Furthermore, the high in vitro solubility of these particles were observed at pH 5 relative to pH 2. The dissolute Fe ions in HCl solution were evaluated by using ferrozine indicator colour complex absorbance at 562 nm. These, experimental data reveals that the significant properties of size and surface chemistry, present with the particles are capable of producing substantial improvement in the bioavailability linked to the direct uptake of the nanoparticle.